Genomic patterns resembling BRCA1- and BRCA2-mutated breast cancers predict benefit of intensified carboplatin-based chemotherapy - Vollebergh, Marieke A; Lips, Esther H; Nederlof, Petra M; Wessels, Lodewyk FA; Wesseling, Jelle; vd Vijver, Marc J; de Vries, Elisabeth GE; van Tinteren, Harm; Jonkers, Jos; Hauptmann, Michael; Rodenhuis, Sjoerd; Linn, Sabine C (Breast cancer research : BCR, 2014)
Introduction BRCA -mutated breast cancer cells lack the DNA-repair mechanism homologous recombination that is required for error-free DNA double-strand break (DSB) repair. Homologous recombination deficiency (HRD) may cause hypersensitivity to DNA DSB-inducing agents, such as bifunctional alkylating agents and platinum salts. HRD can be caused by BRCA mutations, and by other mechanisms. To identify HRD, studies have focused on triple-negative (TN) breast cancers as these resemble BRCA1 -mutated breast cancer closely and might also share this hypersensitivity. However, ways to identify HRD in non- BRCA -mutated, estrogen receptor (ER)-positive breast cancers have remained elusive. The current study provides evidence that genomic patterns resembling BRCA1- or BRCA2 -mutated breast cancers can identify breast cancer patients with TN as well as ER-positive, HER2-negative tumors that are sensitive to intensified, DSB-inducing chemotherapy. Methods Array comparative genomic hybridization (aCGH) was used to classify breast cancers. Patients with tumors with similar aCGH patterns as BRCA1 - and/or BRCA2 -mutated breast cancers were defined as having a BRCA-like CGH status, others as non-BCRA-like CGH . Stage-III patients (n = 249) had participated in a randomized controlled trial of adjuvant high-dose (HD) cyclophosphamide-thiotepa-carboplatin (CTC) versus 5-fluorouracil-epirubicin-cyclophosphamide (FE 90 C) chemotherapy. Results Among patients with BRCA-like CGH tumors (81/249, 32%), a significant benefit of HD-CTC compared to FE 90 C was observed regarding overall survival (adjusted hazard ratio 0.19, 95% CI: 0.08 to 0.48) that was not seen for patients with non-BRCA-like CGH tumors (adjusted hazard ratio 0.90, 95% CI: 0.53 to 1.54) ( P = 0.004). Half of all BRCA-like CGH tumors were ER-positive. Conclusions Distinct aCGH patterns differentiated between HER2-negative patients with a markedly improved outcome after adjuvant treatment with an intensified DNA-DSB-inducing regimen (BRCA-like CGH patients) and those without benefit (non-BRCA-like CGH patients).